PURCHASING DECISION OF PROPERTY BUYERS: THE HOUSING QUALITY, FINANCIAL CAPABILITIES, AND GOVERNMENT POLICIES STUDIES - Kenn, Jhun Kam; Tze, Shwan Lim; Li, Danielle Ping Yoong; Fuey, Lin Ang; Boon, Tik Leong (PLANNING MALAYSIA, 2021)
There are generally three types of house buyers called owner-occupiers, investors,and speculators. However, various factors that affect their decision to purchase a house. The research aims to identify the main factors that will affect the purchase decision of property buyers. Factors such as environmental factors, financial factors, governmental factors, subjective norms, and physical design factors will affect their decision to purchase. The research technique used is quantitative research. Descriptive analysis and inferential analysis to analyse the hypothesis. Based on the findings, the factors that showed to be statistically significant are the environmental, governmental, and subjective norm factors. Environmental factor has a positive influence towards the purchasing decision of dwelling while governmental and subjective norm factor has a negative influence onthe purchasing decision of residential properties. The regression model findings from this research show not only governmentimposed regulation could significantly affecting the purchasers’ decision, however, environmental and subjective norm factors play a major role in this matter. This information is beneficial to developers that have the intention to construct dwellings in the future. Developers can take into consideration all the significant factors before deciding on the location for their future development.